ASSOCIATION OF POLYMORPHISMS GLN192ARG PON1 AND S3238G APOC3 IN WOMEN WITH CORONARY HEART DISEASE AND DIABETES MELLITUS TYPE 2 AND HYPOTHYROIDISM - A. P. Fyodorova; O. V. Serebryakova; D. M. Serkin; N. N. Strambovskaya; B. S. Pushkarev (SINAPS LLC, 2017)
Objective: to determine the frequency of alleles and genotypes of gene polymorphism PON1 - Gln192Arg A> G and ApoC3 - 3238C> G in women with coronary heart disease (CHD) and diabetes mellitus type 2 (DM 2) and hypothyroidism, to determine the odds ratio (OR) andrelative risk (RR) of CHD depending on the genetic characteristics in this group of patients. Material and Methods: the studied 108 patients with stable angina II-III functional class, 35 of which have a combination of type 2 diabetes and hypothyroidism - 1 comparison group,36 women were with type 2 diabetes - 2 comparison group, 37 women with hypothyroidism - Group 3 comparison. The control group included 42 patients with stable angina II-III functional class without pathology of carbohydrate metabolism and the normal function of the thyroidgland. In addition, to eliminate the influence of hypothyroidism factor 4 comparison group was created (1 + 2 group), to avoid the influence of diabetes factor - 5 comparison group (1 + 3 group). Determined PON1 polymorphisms - Gln192Arg A> G and ApoC3 - 3238C> G bypolymerase chain reaction.Results: in women with coronary heart disease combined with type 2 diabetes is more common homozygous carriers of AA genotype polymorphism Gln192Arg PON1 (p = 0.03 for group 2, P = 0.04 for the 4 groups, respectively), while OR was 9.8 ( 95% CI,1,15-84,8) 2 group and 7.5 (95% CI, 0,9-60,4) for group 4, respectively. OR CHD was 2.11 (95% CI, 1.4-3.0) and 1.54 (95% CI, 1,2-1,95) 2 and group 4, respectively. In patients with coronary artery disease combined with type 2 diabetes showed more frequent carriers of the allele C (p = 0.02) and CG genotype polymorphism S3238G APOC3 (p = 0.01). OR 2 groups was 2.8 (95% CI, 1,0-7,8) for 4 groups - 2.7 (95% CI, 1,18-6,4). OR for CHD patients 4 groups was 1.5 (95% CI, 1,0-2,3).Conclusion: the association of genotype polymorphisms Gln192Arg PON1 and S3238G APOC3 in women with coronary heart disease in the background with type 2 diabetes. The presence of the homozygous genotype PON1-AA increases the risk of coronary heart disease in women with type 2 diabetes by 1.5-2 times, carriage heterozygous genotype ApoC3-CG increases the risk of coronary heart disease 1.5 times. Association of polymorphisms with hypothyroidism submitted against the background of coronary heart disease has been identified.